The Role of Tax Avoidance and Sustainability Reporting in Mediating the Influence of Board Diversity on Financial Performance - Febrianti, Pande Kadek Vina; Purnamawati, I Gusti Ayu; Darmawan, Nyoman Ari Surya (Dinasti Publisher, 2025)
This study examines companies in Indonesia Stock Exchange (IDX), specifically those operating in the financial sector during the years 2020 to 2023. It offers an in-depth perspective concerning the correlation of board diversity and financial performance, considering tax avoidance and sustainability reporting as mediating factors. The study sample consists of 156 observations, selected through a purposive sampling method under a non-probability sampling approach. Secondary data were gathered through document analysis and literature review. Panel data was utilized for analysis, and carried out with the assistance of STATA software. It was found that board diversity does not play a significant role in influencing financial performance. Moreover, tax avoidance and sustainability reporting do not play a statistically significant mediating role in the correlation between board diversity and financial performance among financial sector companies listed on the IDX during the 2020-2023